Design and Realization of Novel GaAs Based Laser Concepts - Germann, Tim David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Semiconductor heterostructures represent the backbone for an increasing variety of electronic and photonic devices, for applications including information storage, communication and material treatment, to name but a few. Novel structural and material concepts are needed in order to further push the performance limits of present devices and to open up new application areas. This thesis demonstrates how key performance characteristics of three completely different types of semiconductor lasers can be tailored using clever nanostructure design and epitaxial growth techniques. All aspects of laser fabrication are discussed, from design and growth of nanostructures using metal-organic vapor-phase epitaxy, to fabrication and characterization of complete devices.
Semiconductor Laser Concepts -- Experimental -- MOVPE Processes -- Edge-Emitting Quantum Dot Lasers -- High-Power Vertical External-Cavity Surface-Emitting Lasers -- Electro-optically Modulated Vertical-Cavity Surface-Emitting Lasers -- Summary and Outlook -- Additional Methods.
Keywords: Physics; Optical materials; Nanotechnology; Physics; Semiconductors; Optical and Electronic Materials; Laser Technology, Photonics; Nanoscale Science and Technology; Nanotechnology